Prevention of Suicide Among Young People - Jugović, Aleksandar L. (Zbornik Instituta za kriminološka i sociološka istraživanja, 2011)
Suicide rates in young people have increased during the past three decades in the world. Suicide accounts for around 6% of all deaths in young males and young females, and it becomes prominent as a cause of death in later adolescence, particularly in young adulthood. Risk factor domains which may contribute to suicidal behaviour include individual and personal vulnerabilities, family adversity, exposure to stressful life events and social, cultural and contextual factors. Frequently, suicidal behaviours in young people appear to be a consequence of multiple risk factors. This paper summarises current knowledge about the main approaches in the prevention of suicide in young people. The majority of suicides in young people are preventable and treatable. A small fraction of suicides are committed by mentally ill persons, and these kinds of suicides are often not preventable. But the majority of suicides are impulsive - a reaction to a very stressful event, for example, a love affair turning badly or financial debt. For young people who find themselves at the margins of their communities, perhaps disengaged from school, perhaps disengaged from their families, those kinds of social circumstances and social stresses we know also to be major risk factors for suicide, and they increase across the adolescent years. There are a number of means to decrease suicide. One is training mental health workers and teachers in the early detection of depression and pre-suicidal behaviour. Another is to reduce alcohol consumption, which is rising, particularly among young people. Educating the media in deglamourising suicide is also vital. Comprehensive multi-sectoral approach in prevention of suicide in young people, including both health and non-health sectors, e.g. education, police, justice, religion, law, politics, and the media.